Dual-mode Antenna Tracking System for Rocket Launch Applications - Fakhri, Muh.; Rahmat, Mirza Zulfikar; Pascawati, Anita; Harsono, Sonny Dwi; Nugroho, Yuniarto Wimbo; Rahardiyanti, Kandi; Rohmah, Nurul Fahrizatul (Jurnal Rekayasa Elektrika, 2024)
Rocket launches are complex events that require tracking antennas to maintain a communication link. This study introduces a hybrid tracking strategy that combines manual and program modes by utilizing a predetermined trajectory of the rocket. Automatic switching between tracking modes ensures ongoing monitoring, even during unexpected trajectory changes with the monopulse approach. The dual parabolic antenna arrangement enables this switching. The system estimates the monopulse ratio from the signal strength of each antenna, allowing automatic program tracking to shift to manual mode when reception concerns arise. Performance evaluations included manual, programmable, and dual-mode tests. The system responded to human input and automatically aligned the antenna with slight elevation errors during the initial phase. Adjusting the initial elevation reduced the error. The mode transition was examined by measuring the antenna radiation patterns and monopulse ratio. The systems performance was evaluated in rocket launches, with the rocket trajectory input into the graphical user interface. The antenna exhibited an azimuthal movement of up to 10 , and the ratio fluctuation values remained within the antennas field of view. After 8.8 seconds, the mode switched from program to manual, indicating that the functioning of the systems functioning was stable.